2012
DOI: 10.1371/journal.pone.0032280
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Corticosteroids and Early Administration of Antiviral Agents for Pneumonia with Acute Wheezing due to Influenza A(H1N1)pdm09 in Japan

Abstract: BackgroundPneumonia patients with wheezing due to influenza A(H1N1)pdm09 were frequently treated with systemic corticosteroids in Japan although systemic corticosteroid for critically ill patients with pneumonia caused by influenza A(H1N1)pdm09 has been controversial. Applicability of systemic corticosteroid treatment needs to be evaluated.Methods/Principal FindingsWe retrospectively reviewed 89 subjects who were diagnosed with influenza A(H1N1)pdm09 and admitted to a national hospital, Tokyo during the pandem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 12 publications
0
36
0
Order By: Relevance
“…There are several anti‐inflammatory agents that have been evaluated for efficacy against severe influenza using murine models, such as the commercially available TNF‐α inhibitor etanercept, corticosteroids, COX2 inhibitors, a TLR4 antagonist (Eritoran), and anti‐HMGB1 mAb . Considering that there is no reason to treat influenza without NAI in daily clinical settings, we are interested in evaluating the adjunctive effects of these agents with NAI therapy against severe influenza.…”
Section: Discussionmentioning
confidence: 99%
“…There are several anti‐inflammatory agents that have been evaluated for efficacy against severe influenza using murine models, such as the commercially available TNF‐α inhibitor etanercept, corticosteroids, COX2 inhibitors, a TLR4 antagonist (Eritoran), and anti‐HMGB1 mAb . Considering that there is no reason to treat influenza without NAI in daily clinical settings, we are interested in evaluating the adjunctive effects of these agents with NAI therapy against severe influenza.…”
Section: Discussionmentioning
confidence: 99%
“…Hematopoietic cell transplant recipients with a pandemic H1N1 influenza infection receiving high-dose glucocorticoids at the time of influenza diagnosis had a reduced risk for mechanical ventilation (49). A recent study has also indicated that systemic corticosteroids together with early administration of antiviral agents in H1N1-infected asthmatics prevent progression to severe pneumonia (50). However, the emerging lines of evidence to demonstrate early therapy of high-dose corticosteroids in strong association with mortality (23,24), increased prevalence of a secondary bacterial infection (24), and prolonged viral shedding (25) raise caution about routine use of corticosteroids in severe H1N1 pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Corticosteroids have been suggested as a potential treatment option for patients undergoing severe IAV infection with accompanied cytokine storm [21][22][23][24][25], while pre-stimulating interferon-associated pathways have been suggested to protect high-risk groups [7,20,26,27].…”
Section: Immune Modulation For the Treatment Of Iav Infectionmentioning
confidence: 99%